MICRONUTRIENT STATUS AND ENERGY INTAKE IN MODERATE ACUTE MALNOURISHED CHILDREN AFTER INTAKE OF HIGH ENERGY NUTRITIONAL SUPPLEMENTS FOR FOUR WEEKS: A RANDOMIZED CONTROLLED STUDY - Nawab, Fouzia; Fatima, Sadia; Nazli, Rubina; Habib, Syed Hamid; Nawab, Sadia; Gerasimidis, Konstantinos (Journal of Ayub Medical College Abbottabad, 2022)
Background: Undernutrition including micronutrient deficiency results in adverse health-related outcomes in children of low-medium income countries. This study aims to explore the effect of four weeks of Lipid-based nutritional supplement (LNS) on energy intake, anthropometry and micronutrient status in moderate acute malnourished children. Methods Thirty-four children with mean age 7.08±1.47 years and a BMI Z score between -2 and -3 SDS were randomized into LNS and Placebo groups in a single blind randomized control trial. Energy intake, fasting blood samples, and anthropometric measurements were obtained prior to and after four weeks of LNS (535 kcal) or Placebo (92kcal) supplementation in addition to their habitual dietary intake. Results: During four weeks of supplementation, energy intake (kcal) [(611±155) to (987±224), p<0.001)], weight (kg) [(17.5±2.83) to (18.1±3.24), p< 0.001], mid-upper arm circumference (cm) [(14.8±0.91) to (15.1±0.84), p=0.005)] and BMI (kg/m2) [(12.9±0.33) to (13.3±0.45), p=0.002] was significantly improved in the LNS group compared to Placebo. A significant increase in hemoglobin (g/ml) [(12.2±1.14) to (13.7±1.69), p<0.01] and iron levels (µg/dl) [(0.36±0.09) to (0.67±0.20), p<0.001] were observed in the LNS group. No significant differences were detected in the copper and zinc levels. Conclusion: Lipid-based nutritional supplement is effective in improving energy intake, nutritional outcomes and iron but not copper and zinc. The trial was registered at www.isrctn.com under reference: ISRCTN147181521.